2012
DOI: 10.1017/s1368980012003849
|View full text |Cite
|
Sign up to set email alerts
|

Fibre intake and evolution of BMI: from pre-pregnancy to postpartum

Abstract: Objective: To evaluate the effect of fibre intake on the evolution of maternal BMI from pregnancy to postpartum and to identify dietary patterns associated with fibre intake. Design: Cohort study. Food intake was obtained using an FFQ. Focused principal component analysis was used focusing on the variables: postpartum weight retention and total dietary fibre intake. Poisson regression models with robust variance were built in order to measure the effect of fibre intake during the postpartum period on obesity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…In contrast, Drehmer et al . ( 29 ) found negative associations between daily fibre consumption and occurrence of obesity among 370 Brazilian pregnant women and observed that those who did not reach the daily recommendation of fibre intake (28 g) (DRI, 2002) had a 30 % higher risk of postpartum obesity compared with those who did reach the recommendation. These authors also showed that the highest contribution of fibre intake came from beans.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Drehmer et al . ( 29 ) found negative associations between daily fibre consumption and occurrence of obesity among 370 Brazilian pregnant women and observed that those who did not reach the daily recommendation of fibre intake (28 g) (DRI, 2002) had a 30 % higher risk of postpartum obesity compared with those who did reach the recommendation. These authors also showed that the highest contribution of fibre intake came from beans.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no known associations with pregnancy overnutrition of copper, it has been considered a potential risk factor in cardiovascular disease [63,64]. High copper intake has also been negatively associated with cognitive function [65]. Undernutrition of copper is uncommon but can result from genetic uptake disorders or deficiency of trace elements from foodstuffs, more common in people consuming a Western diet [66].…”
Section: Micronutrition During Gestation and Lactationmentioning
confidence: 99%
“…They were evaluated during pregnancy and in the postpartum period up to the fifth month [9]. In order to estimate food intake during pregnancy [13] and during the postpartum period [14], a previously validated [15] Food Frequency Questionnaire (FFQ) was used in the present study.…”
Section: E T H O D Smentioning
confidence: 99%
“…Buss et al [13] and Giacomello et al [15] [18]. After the release of the TACO, all analyses related to food consumption in the ECCAGe were carried out using this table [14,19].…”
Section: E T H O D Smentioning
confidence: 99%